pH Dependence on Colorimetric Detection of Hg2+ by Histidine-Functionalized Gold Nanoparticles - Dewi Eviane; Dwi Siswanta; Sri Juari Santosa (Indonesian Journal of Chemistry, 2020)
In this study, we successfully developed gold nanoparticles capped with histidine (His-AuNPs) for Hg2+ detection using trisodium citrate as the reducing agent. The optimum pH for the detection of Hg2+ by His-AuNPs was 12. The addition of Hg2+ to the His-AuNPs caused the color change from red to black-blue, which is readily detectable by the naked eye. This color change is followed by a decrease in the intensity of the primary Surface Plasmon Resonance (SPR) peak at a wavelength (λ) of 525 nm and an increase in the secondary peak at λ = 650 nm. His-AuNPs effectively detected Hg2+ with limits of detection and quantitation of 1.77 µM and 5.89 µM, respectively. His-AuNPs exhibited good performance for the detection of Hg2+ in waste water collected from a steel industrial facility in Banten Province, with a recovery and a percent relative standard deviation of 115% and 1.02%, respectively.